1988
DOI: 10.1128/iai.56.10.2766-2768.1988
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the gastrointestinal microflora on induction and maintenance of oral tolerance to ovalbumin in C3H/HeJ mice

Abstract: The effect of the digestive microflora on oral tolerance to ovalbumin was studied by using axenic (germfree) and conventional C3H/HeJ mice. In contrast to reported results of studies with sheep erythrocytes, oral administration of ovalbumin induced tolerance in axenic mice, but the maintenance of tolerance was found to be of shorter duration than was with conventional mice. These data indicate that the contribution of the microflora to oral tolerance depends on the antigen used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(52 citation statements)
references
References 15 publications
2
50
0
Order By: Relevance
“…25 When germ-free mice are colonized with either a mixture of different bacterial strains, a mixture of Clostridium species or with Bacteroides fragilis the proportion of FOXP3 + Treg cells in the gut is increased. [23][24][25][26] These experiments also show that bacterial stimulation induces de novo generation of FOXP3 + pTreg cells because higher proportions of the Helios neg Treg cells were found in the gut of colonized mice compared with in germ-free mice. 25,26 In developing countries, the first bacteria that colonize the infantile gut include Escherichia coli, enterobacteria (other than E. coli) and enterococci.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…25 When germ-free mice are colonized with either a mixture of different bacterial strains, a mixture of Clostridium species or with Bacteroides fragilis the proportion of FOXP3 + Treg cells in the gut is increased. [23][24][25][26] These experiments also show that bacterial stimulation induces de novo generation of FOXP3 + pTreg cells because higher proportions of the Helios neg Treg cells were found in the gut of colonized mice compared with in germ-free mice. 25,26 In developing countries, the first bacteria that colonize the infantile gut include Escherichia coli, enterobacteria (other than E. coli) and enterococci.…”
Section: Discussionmentioning
confidence: 60%
“…[18][19][20] Interaction between PD-L1 and its receptor programmed cell death 1 (PD-1) expressed on activated T cells impede the T-cell receptor signalling pathway within the T cell, 18,21 which can lead to differentiation into FOXP3 + Treg cells. 18,19,22 Experiments in germ-free mice have shown that bacterial colonization of the intestine is of great importance for the induction of Treg cells, [23][24][25][26] as these mice have a lower proportion of and less suppressive FOXP3 + Treg cells in the gut compared with conventional mice. 25 When germ-free mice are colonized with either a mixture of different bacterial strains, a mixture of Clostridium species or with Bacteroides fragilis the proportion of FOXP3 + Treg cells in the gut is increased.…”
Section: Discussionmentioning
confidence: 99%
“…An important feature of certain normal intestinal bacteria is that they might modulate the handling of food antigens by the gut immune system, increasing the capacity to develop tolerance. Mice devoid of a normal intestinal microbiota develop oral tolerance to certain antigens like ovalbumin, but the suppression is weaker and lasts a shorter time [25,26]. The rats colonized with L. plantarum in addition to E. coli exhibited a marked and persistent increase in cells expressing the IL-2 receptor a-chain (CD25) in the lamina propria, presumably representing activated T cells.…”
Section: Discussionmentioning
confidence: 99%
“…These commensals naturally colonize the intestinal tract, which is one important quality that makes them candidates for use as probiotics (Massi et al, 2004). In addition, autochthonous bacteria are involved in the development and maintenance of oral tolerance against food antigens (Moreau and Corthier, 1988;Tanaka and Ishikawa, 2004). However, commensal bacterial species would not be expected to stimulate mucosal or systemic immune responses, at least not as long as they do not breach the intestinal barrier or enter the bloodstream (Scharek et al, 2005;Westendorf et al, 2005).…”
Section: Introductionmentioning
confidence: 99%